Trends in utilization and costs of BRCA testing among women aged 18–64 years in the United States, 2003–2014 - Chen, Zhuo; Kolor, Katherine; Grosse, Scott D; Rodriguez, Juan L; Lynch, Julie A; Green, Ridgely Fisk; Dotson, W David; Bowen, M Scott; Khoury, Muin J (Nature Publishing Group, 2017)
Purpose We examined 12-year trends in BRCA testing rates and costs in the context of clinical guidelines, national policies, and other factors. Methods We estimated trends in BRCA testing rates and costs from 2003 to 2014 for women aged 18–64 years using private claims data and publicly reported revenues from the primary BRCA testing provider. Results The percentage of women with zero out-of-pocket payments for BRCA testing increased during 2013–2014, after 7 years of general decline, coinciding with a clarification of Affordable Care Act coverage of BRCA genetic testing. Beginning in 2007, family history accounted for an increasing proportion of women with BRCA tests compared with personal history, coinciding with BRCA testing guidelines for primary care settings and direct-to-consumer advertising campaigns. During 2013–2014, BRCA testing rates based on claims grew at a faster rate than revenues, following 3 years of similar growth, consistent with increased marketplace competition. In 2013, BRCA testing rates based on claims increased 57%, compared with 11% average annual increases over the preceding 3 years, coinciding with celebrity publicity. Conclusion The observed trends in BRCA testing rates and costs are consistent with possible effects of several factors, including the Affordable Care Act, clinical guidelines and celebrity publicity.